Do Temporary Demand Shocks Have Long-Term Effects for Startups?. (19th May 2022) - Hvide, Hans K; Meling, Tom G
Abstract: Using procurement auctions and register data, we find that temporary demand shocks have long-term effects for startups. Startups that win a procurement auction have 20% higher sales and employment and are more profitable than startups that narrowly lose an auction, even several years after the contract work has ended. There are no such effects for mature firms. The effects for startups are large: about 50% of the contract value is transmitted into long-term sales. Our analysis suggests learning-by-doing as a plausible mechanism. Overall, our results point to the importance of path dependence in shaping the long-term outcomes of startups. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online